Pengaruh Kualitas Sumber Daya Manusia dan Manajemen Perawatan Kapal Terhadap Sistem Manajemen Keselamatan Kapal Dimediasi oleh Kinerja Staff Galangan Kapal pada PT. Dok Pantai Lamongan - Ginting, Purnomo Ramadhani; Kania, Dinar Dewi; Indrawan, Rully; Setiawan, Edhie Budi (Ranah Research : Journal of Multidisciplinary Research and Development, 2025)
This study aims to analyze the effect of human resource quality and ship maintenance management on the ship safety management system with the performance of shipyard staff as a mediating variable at PT. Dok Pantai Lamongan. Human resource quality and maintenance management are strategic factors in minimizing accident risks and ensuring operational safety in shipping. This research uses a descriptive quantitative approach with inferential analysis through Structural Equation Modeling (SEM) methods. Data were collected from 218 respondents who are shipyard staff directly involved in maintenance and operational activities. The results indicate a significant positive direct effect between human resource quality and ship maintenance management on shipyard staff performance and the ship safety management system. Furthermore, there is a significant positive direct effect between shipyard staff performance and the ship safety management system, as well as a significant positive indirect effect between human resource quality and ship maintenance management on the ship safety management system, mediated by the shipyard staff performance. These findings emphasize that improving human resource quality through training, work discipline, and strengthening a structured maintenance management system will optimize the performance of shipyard staff and ultimately strengthen the ship safety system. This study implies that PT. Dok Pantai Lamongan needs to emphasize human resource competency improvement programs and digitally integrated maintenance management to ensure the sustainability of ship operational safety